The fish resources of the ocean. Fishing News (Books) Ltd., Surrey, England, xi+special map section+255 pp. Price Â£ 10.50. - Qasim, S Z (Indian Journal of Fisheries, 2011)
Gulland, J. A. [Compiler and Editor] 1971. The fish resources of the ocean. Fishing News (Books) Ltd., Surrey, England, xi+special map section+255 pp. Price Â£ 10.50.